A call for evidence-based trauma care: BestBETs. (October 2015) - Smith, Jason E; Mackway-Jones, Kevin; Wylie, Katharine; Carley, Simon
In order to achieve optimal care for patients, it is essential that care is based on the best available evidence. Best Evidence Topics are short digests of the available research, summarised in a systematic format, accessible for the busy professional. Trauma will now add to the collection of journals that feature BestBETs. All clinicians involved in the care of the injured can contribute to this process by defining and disseminating the knowledge basis for our clinical practice. The invitation for you to derive, submit and publish is now open.